2009
DOI: 10.1097/wnr.0b013e32831af055
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity in the primate globus pallidus during smooth pursuit eye movements

Abstract: Although the roles of the basal ganglia in the control of saccadic eye movements have been extensively examined, little is known about their roles in smooth pursuit. Recent anatomical data suggest that, like somatic movements, smooth pursuit may also be regulated by signals through the basal ganglia thalamocortical pathways. To understand whether the basal ganglia, especially the globus pallidus (GP), could play roles in pursuit, we examined the firing of individual GP neurons when monkeys performed smooth pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…However, one fairly direct way of studying the activity of the corticostriatal loop is the measurement of anticipatory eye movement during an oculomotor task. Indeed, anticipatory saccadic and smooth pursuit eye movements have extensively been studied in primates [21]; [16][17], [20], [78][79]; [10]; [11]; [14]; [13]; [9]; [12]; [15]; [8] and involve both basal ganglia [80][81]; [82]; [46]; [83], [84]; [85]; [86], [87][88], [89]; [90]; [91] and frontal cortex [24]; [23]; [26]; [22]; [25]. Neuronal processes driving eye movements have been studied in detail and, although some unanswered questions still persist, they are among the best described neural systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, one fairly direct way of studying the activity of the corticostriatal loop is the measurement of anticipatory eye movement during an oculomotor task. Indeed, anticipatory saccadic and smooth pursuit eye movements have extensively been studied in primates [21]; [16][17], [20], [78][79]; [10]; [11]; [14]; [13]; [9]; [12]; [15]; [8] and involve both basal ganglia [80][81]; [82]; [46]; [83], [84]; [85]; [86], [87][88], [89]; [90]; [91] and frontal cortex [24]; [23]; [26]; [22]; [25]. Neuronal processes driving eye movements have been studied in detail and, although some unanswered questions still persist, they are among the best described neural systems.…”
Section: Discussionmentioning
confidence: 99%
“…Basal ganglia outputs project to the FEF and SEF through the thalamus, and Cui et al (2003) described a possible pursuit loop between the caudal FEF and basal ganglia (Figure 15, thick dashed lines, also Lynch and Tian, 2006). Yoshida and Tanaka (2009) suggested that this loop may contribute to maintaining normal pursuit gain.…”
Section: Preliminary Results Of Clinical Applicationmentioning
confidence: 99%
“…The basal ganglia are necessary for efficient and accurate pursuit performance possibly by contributing to maintaining normal pursuit gain (Cui et al, 2003; Lynch and Tian, 2006; Yoshida and Tanaka, 2009) and by inducing the priming effects on visual motion responses of SEF and caudal FEF neurons (Figure 15, thick dashed lines). The latter may be necessary for fast and “automatic” selection of pursuit target during memory-based pursuit (see Memory-Based Smooth-Pursuit; Figure 14B1, *).…”
Section: Functional Considerationsmentioning
confidence: 99%
“…In the following, reward-related signals have been identified also in the visual cortex, including the primary visual cortex V1 (Serences, 2008;Stanisor et al, 2013). Furthermore the basal ganglia play an important role in the control of saccades by reward (Hikosaka, 2007;Hikosaka, Takikawa, & Kawagoe, 2000) and pursuit-related signals have been identified recently (Basso, Pokorny, & Liu, 2005;Yoshida & Tanaka, 2009).…”
Section: Neurophysiological Basismentioning
confidence: 97%